Pengaruh Packaging Dan Label Halal Terhadap Keputusan Pembelian Produk Pop Mie Di Wilayah Surakarta - Monyka Dayu Astuti; Winda Saputri; Taufik Nur Muftianto (Journal Economic Excellence Ibnu Sina, 2024)
The aim of this study is to explore the impact of halal packaging and labels on purchasing decisions for Pop Mie products in Surakarta. This research adopts a quantitative method, collecting primary data through the distribution of questionnaires to 52 respondents. Analysis is conducted using Intelligent Partial Least Squares (PLS) to evaluate hypotheses, employing a quantitative approach. The results of the PLS analysis indicate that halal packaging and labels have a significant positive influence on purchasing decisions.